Systems Approaches to Combating Wildlife Trafficking: Expanding Existing Frameworks to Facilitate Cross-Disciplinary Collaboration - Browne, Christine; Ronis, Emily M.; Miller, Jennifer R. B.; Kapetanakos, Yula; Gibbs, Samantha; Hendrix, Tatiana; Carlson Bremer, Daphne (Frontiers in Conservation Science, 2021)
Wildlife trafficking is a complex conservation issue that threatens thousands of species around the world and, in turn, negatively effects biodiversity and human well-being. It occurs in varied social-ecological contexts; includes numerous and diverse actors along the source-transit-destination trade chain, who are involved in illicit and often covert human behaviors driven by interacting social, economic, cultural, and political factors; and involves numerous stakeholders comprising multiple sectors and disciplines. Such wicked problems can be difficult to define and usually lack simple, clear solutions. Systems thinking is a way to understand and address complex issues such as wildlife trafficking and requires multisectoral, cross-disciplinary collaboration to comprehensively understand today’s increasingly complex problems and develop holistic and novel solutions. We review methods utilized to date to combat wildlife trafficking and discuss their strengths and limitations. Next, we describe the continuum of cross-disciplinarity and present two frameworks for understanding complex environmental issues, including the illegal trade in wildlife that can facilitate collaboration across sectors and disciplines. The Open Standards for the Practice of Conservation provides guidance and tools for defining complex social-ecological systems and identifying strategic points of intervention. One Health focuses on the nexus of human, wildlife and environmental health, and can provide a framework to address concerns around human-wildlife interactions, including those associated with the illegal wildlife trade. Finally, we provide recommendations for expanding these and similar frameworks to better support communication, learning, and collaboration in cross-disciplinary efforts aimed at addressing international wildlife trafficking and its intersections with other complex, global conservation issues.